Retrospective analysis of the adverse events during intra-operative and post-operative period in patients who received anesthesia at a tertiary care center in India - Shah, Kshama; Tiwaskar, Shilpa; Rao, Namrata; Kulkarni, Vivek; Ranade, Rahul; Gore, Shivanjali (International Surgery Journal, 2024)
Background: Anesthesia is a critical component of modern surgical procedures ensuring patient comfort and safety during surgery. With the increase in life expectancy, more and more geriatric population with various systemic comorbidities have been coming for surgeries. Along with the newer advances in surgical fields, there is increasing demand on the anesthetists to handle complicated cases with innovative solutions. Despite all efforts by a skillful anesthetist, adverse events are bound to occur which needs to be analysed to prevent such adverse events in the future. Hence, this study aims to analyse the adverse events occurring in intra-operative and post-operative period who received anesthesia in our tertiary care centre. Methods: This study is a retrospective cross-sectional study of 5-year duration from January 2018 to January 2023 done at Bhaktivedanta hospital and research institute post obtaining approval from the institutional ethics committee. A total of 163 patients who developed perioperative adverse events were included in the study and their nature of adverse events were analysed. The data was obtained from the registers of the anesthesia department and descriptive statistical analysis of the data was done accordingly. Results: Most common adverse events were of cardiovascular and respiratory origin, followed by miscellaneous and regional anesthesia adverse events and then, very few drug-related adverse events. The patients who developed these adverse events were evidently of ASA grade I and II, implying no direct correlation between adverse events and grading. Conclusions: Reporting and analysis of the adverse events will help better understanding of the lacunae of the reporting system as well as in the development of quality improvement strategies in the future.